Proceedings of the 26th Annual ACM Symposium on User Interface Software and Technology 2013
DOI: 10.1145/2501988.2501998
|View full text |Cite
|
Sign up to set email alerts
|

Pursuit calibration

Abstract: Eye gaze is a compelling interaction modality but requires user calibration before interaction can commence. State of the art procedures require the user to fixate on a succession of calibration markers, a task that is often experienced as difficult and tedious. We present pursuit calibration, a novel approach that, unlike existing methods, is able to detect the user's attention to a calibration target. This is achieved by using moving targets, and correlation of eye movement and target trajectory, implicitly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
2

Relationship

4
6

Authors

Journals

citations
Cited by 127 publications
(38 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Early works introduced the principle as enabling "pointing without a pointer" and "motion-pointing" [9,37,38], inspired by perceptual control theory [19] and naturally harmonic human motor behaviour [11]. Recent work adopted motion correlation for gazeand gesture-based interaction [5,8,25,33,34], leveraging human natural ability to smoothly follow motion with their eyes and hands. This prior body of work, recently reviewed in depth by Velloso et al [32], demonstrated advantages of motion correlation: the high discoverability of the available gestures as they are continuously displayed [5,9]; implicit coupling of input and output coordinate spaces without need for calibration [8,34]; usability with feedback modalities that are not suited for pointing [33,38]; no split of attention between a cursor and a target [9]; and the capacity for multi-user input [5].…”
Section: Motion Correlation As Input Methodsmentioning
confidence: 99%
“…Early works introduced the principle as enabling "pointing without a pointer" and "motion-pointing" [9,37,38], inspired by perceptual control theory [19] and naturally harmonic human motor behaviour [11]. Recent work adopted motion correlation for gazeand gesture-based interaction [5,8,25,33,34], leveraging human natural ability to smoothly follow motion with their eyes and hands. This prior body of work, recently reviewed in depth by Velloso et al [32], demonstrated advantages of motion correlation: the high discoverability of the available gestures as they are continuously displayed [5,9]; implicit coupling of input and output coordinate spaces without need for calibration [8,34]; usability with feedback modalities that are not suited for pointing [33,38]; no split of attention between a cursor and a target [9]; and the capacity for multi-user input [5].…”
Section: Motion Correlation As Input Methodsmentioning
confidence: 99%
“…In addition to using it as a calibration-free gaze interaction technique, Pursuits can also be used for calibration. Pfeuffer et al [25] introduced a method to calibrate the eye tracker as users follow onscreen moving targets. Similarly, Celebi et al [3] used Pursuits for eye tracker calibration.…”
Section: Applications Of Pursuitsmentioning
confidence: 99%
“…Motion-matching is an alternative selection mechanism to pointing, relying on the ability of users to couple with motion displayed at the interface [57]. First explored by Williamson and Murray-Smith [63], motion-matching has been used with a variety of different input modalities, including the mouse [63,24], eye gaze [47,59,22], and recently touchless interaction [13,17,16]. PathSync demonstrated the discoverability, intuitiveness and multi-user capacity of motion-matching for hand-based gestures [13], while TraceMatch showed users' capacity to synchronise using different input modalities [16].…”
Section: Background and Related Workmentioning
confidence: 99%